Potential of in vivo- and in vitro-cultured entomopathogenic nematodes to infect Lobesia vanillana (Lepidoptera: Tortricidae) under laboratory conditions. - Francois du Preez (Public Library of Science (PLoS), 2021)
Entomopathogenic nematodes (EPNs) have been successfully applied as biological control agents against above ground and soil stages of insect pests. However, for commercial application, it is crucial to mass culture these nematodes using in vitro liquid culture technology, as it is not attainable when using susceptible insects as hosts. Lobesia vanillana (Lepidoptera: Tortricidae) is regarded a sporadic pest of wine grapes in South Africa. The in vivo- and in vitro-cultured South African EPNs, Steinernema yirgalemense and Steinernema jeffreyense (Rhabditida: Steinernematidae), were evaluated against larvae and pupae of L. vanillana in laboratory bioassays. For larvae, high mortality was observed for all treatments: In vitro-cultured S. yirgalemense (98%) performed better than S. jeffreyense (73%), while within in vivo cultures, there was no difference between nematode species (both 83%). No significant difference was detected between in vivo- and in vitro cultures of the same nematode species. The LD50 of the in vitro-cultured S. yirgalemense, was 7.33 nematodes per larva. Mortality by infection was established by dissecting L. vanillana cadavers and confirming the presence of nematodes, which was > 90% for all treatments. Within in vitro cultures, both S. yirgalemense and S. jeffreyense were able to produce a new cohort of infective juveniles from L. vanillana larvae. Pupae, however, were found to be considerably less susceptible to EPN infection. This is the first study on the use of EPNs to control L. vanillana. The relative success of in vitro-cultured EPN species in laboratory assays, without any loss in pathogenicity, is encouraging for further research and development of this technology.